An Automatic Heliostat for Non-Stationary Target - Zhang, Jiabin. (2017)
Abstract: Heliostats are widely used to concentrate sunlight for solar thermal power generation. However, in nearly all cases, the targets for heliostats are fixed. This thesis describes the design, fabrication, control, and testing of a new heliostat system that reflects sunlight onto a moving target for the purpose of melting snow and ice. One novel aspect of the system is that it uses one "Pixy" intelligent infrared camera for tracking the sun and a separate Pixy for tracking the target. For automated operation, we devised a scheme consisting of two working modes. The first mode is the searching mode, in which the two Pixy cameras search for the sun and the moving ground target respectively in predefined routes. The second mode is the reflecting mode, which the Pixys continuously track the sun and the target to provide direction information. Using information from cameras, the controller controls the two gear motors to regulate the azimuth and the elevation of the mirror to direct the sun onto the target. Tests in a simulated environment demonstrate that the heliostat reflects the sun onto the target with minimal errors under appropriate conditions.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Mechanical Engineering.; Advisor: William Messner.; Committee: Jason Rife, and Usman Khan.; Keyword: Mechanical engineering.